Mobilidade humana e trabalho: a situação de brasileiros em Lethem (Gy) - Almeida, Júlia Maria Corrêa Almeida (2016)
The aim of this study is to understand the processing of Brazilian human labor mobility, in search of work that occurs in the border of Brazil with Co-operative Republic of Guyana, in the Brazilian city of Bonfim, in Roraima, with the city of Lethem, in Guyana. In this context, this study demonstrates how the occurrence of human mobility and the ordinance of labor universe are concretized in the context of globalization of economy, providing a greater understanding of the multidisciplinary theme with different perspectives, setting concepts able to give attention to the complexity of the migratory phenomenon that occurs in this cross-border, emphasizing the daily relationships of the population from this region, through the bonding of these trans-local communities, as well as the transformations that occur in this geographical space that concretely has provided economic, cultural , political and social changes to the border. Guyana concentrates Brazilian migrant workers, legitimizing an existent dynamic between the two sides of the city. It is in this perspective that we led our research, highlighting experiences of people who transit in this bordering region, evidencing the existence, the dynamic, the particularity about this flow of Brazilian workers who move to the neighboring country.